Load shedding scheme for islanded distribution network with flexible load selection and power changes / Ja’far Saifeddin Abdelhafiz Jallad - Ja’far Saifeddin , Abdelhafiz Jallad (2018)
Islanding is one of the most important issue in modern distribution networks. Islanding condition usually results in a large excursion of a distribution network’s frequency and voltage due to the imbalance between generation and load demand. In this case, the distributed generation (DG) units need to operate at a maximum output power to reduce a power deficit in the islanding operation of the distribution network. When the output power of the DG units fails to compensate for the imbalance of power, load shedding can be used to maintain the power system’s stability via the curtailment of partial loads in some parts of the system. The main aim of this research is to address two important aspects; increasing the reliability of the system by maximizing the remaining load by improving the voltage bus after the application of load shedding in the planning mode, and detecting and estimating a new power deficit during the UFLS process in the operation mode with flexible load selection. In order to realize the first aspect, a combination of particle swarm optimization (PSO) algorithm and firefly algorithm (FA) can be used to maximize the amount of remaining load and the voltage stability index (SI) in the distribution network. A metaheuristic algorithm in the UFLS scheme can be used to select the best load combination in real time. Taking into account the time execution, the artificial neural network (ANN) model was constructed based on the daily load plots. The second aspect involve monitoring the overshooting signal of the second frequency derivative of the center of inertia so that we can detect new power deficits during the load shedding process. An equivalent system inertia constant needs to be estimated in order to quantify the new power deficit. In this method, the calculated total load shed amount is to be shed properly using binary PSO optimization for the selection of the best load combination. The capabilities of the proposed methods can be assessed using the IEEE 33 - bus radial distribution system with different types of DGs, and a part of Malaysia’s distribution network was selected to validate the proposed methods in MATLAB and PSCAD/EMTDC X4 4.3.1.0. The simulation results confirmed that the proposed hybrid algorithm, in the context of the planning load shedding scheme, is able to stabilize the voltage and frequency of an islanded distribution network with the maximum remaining load while improving the voltage buses. The proposed UFLS scheme-I in operation mode is also capable of recovering the network frequency within allowed limits (47.5-52.5 Hz). Furthermore, during the sudden changing power during the shedding process, the proposed UFLS scheme-II can still recover the frequency by shedding the required loads within (0.2 seconds) without overshooting the frequency.